AN X-GREEDY ALGORITHM WITH WEAKNESS PARAMETERS - Causey, Ryan; Dilworth, Stephen J; Gogyan, Smbat; Kutzarova, Denka (Comptes rendus de l'Academie bulgare des Sciences, 2015)
We prove that in the space [mathematical expression not reproducible], where [F.sub.n] are finite-dimensional smooth spaces, the X-Greedy Algorithm with weakness parameters converges for some special dictionaries.Key words: greedy algorithm2010 Mathematics Subject Classification: Primary 41A65, Secondary 42A10, 46B20